Analisis Strategi Personal Selling dalam Kegiatan Komunikasi Pemasaran untuk Upaya Meningkatkan Keputusan Pembelian Produk pada CV Entrepreneur Muda Indonesia - Ahmad Dimyati; Dedek Kumara; Mutmainnah Mutmainnah (Journal on Education, 2024)
This research is about "Analysis of Personal Selling Strategies in Marketing Communication Activities to Efforts to Improve Product Purchasing Decisions on CV Entrepreneur Muda Indonesia ". The type of research carried out is qualitative with informants or sources in this research in the form of strategic parts in the sales division of Indonesian Young Entrepreneur CVs. . Research data will be displayed using SWOT analysis with the EFAS and IFAS methods, and the SWOT Matrix, to determine the personal selling strategy carried out by CV Entrepreneur Muda Indonesia. Based on the SWOT diagram through various strategies that have been arranged in the SWOT table. Three alternative strategies were chosen according to Quadrant I conditions based on the SWOT Diagram, namely; Adding new features that are not available, Reorganizing the Sales Team so that it acquires equally/focuses on a category, Evaluating the form of promotions and their results to create new promotions.